Nioella nitratireducens gen. nov., sp nov., a novel member of the family Rhodobacteraceae isolated from Azorean Island - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Khieu, Thi-Nhan; Son, Chu Ky; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-negative, non-spore forming, rod-shaped aerobic bacterium, designated SSW136(T), was isolated from a surface seawater sample collected at Espalamaca (in Faial Island), Azores. Growth was found to occur from 10 to 37 A degrees C, pH 6.0-8.0, and with 2-11 % of NaCl. 16S rRNA gene sequence indicated that the strain SSW136(T) belongs to the family Rhodobacteraceae. Strain SSW136(T) exhibited 96.3, 95.9, 95.7 and 95.5 sequence similarity to the type strains Oceanicola litoreus M-M22(T), Roseovarius aestuarii SMK-122(T), Marivita geojedonensis DPG-138(T), and Pseudoruegeria aquimaris SW-255(T) respectively. Neighbour-joining and maximum-parsimony phylogenetic trees based on 16S rRNA gene sequences revealed that strain SSW136(T) was affiliated to the family Rhodobacteraceae and formed a separate branch. The G+C content was 63.5 mol%. The major respiratory quinone was found to be Q-10. The polar lipids of strain SSW136(T) consisted of phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, two unidentified aminolipids and three unidentified phospholipids. The major fatty acids were C-18:1 omega 7c (46.5 %), Cyclo-C-19:0 omega 8c (16.0 %) and C-16:0 (12.8 %). On the basis of the morphological, genotypic, chemotaxonomic characteristics and low DNA-DNA relatedness, strain SSW136(T) is proposed to represent a novel genus and novel species, Nioella nitratireducens gen. nov., sp. nov., in the family Rhodobacteraceae. The type strain is SSW136(T) (=KCTC 32417(T) = NCIM 5499(T)).
Keywords: Espalamaca; Nioella nitratireducens; Novel genus and species; Polyphasic taxonomy; Seawater